2023
DOI: 10.1111/hex.13936
|View full text |Cite
|
Sign up to set email alerts
|

Public values to guide childhood vaccination mandates: A report on four Australian community juries

Chris Degeling,
Julie Leask,
Katie Attwell
et al.

Abstract: ObjectiveGovernments use vaccination mandates, of different degrees of coerciveness, to encourage or require childhood vaccination. We elicited the views of well‐informed community members on the public acceptability of using childhood vaccination mandates in Australia.MethodsFour community juries were conducted in Canberra, Launceston, Cairns and Melbourne, Australia between 2021 and 2022. We recruited 51 participants from diverse backgrounds, genders and ages through random digit dialling and social media. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These findings are ratified by a study of four Australian community juries who supported mandates for childhood vaccination from the perspective of the collective, but recommended mandates be part of a co-ordinated intervention including a range of strategies and incentives. While both NJNPay and NJNPlay were supported, restricting access to financial incentives for parents were preferred to restricting access to a child’s education [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are ratified by a study of four Australian community juries who supported mandates for childhood vaccination from the perspective of the collective, but recommended mandates be part of a co-ordinated intervention including a range of strategies and incentives. While both NJNPay and NJNPlay were supported, restricting access to financial incentives for parents were preferred to restricting access to a child’s education [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the public health evidence for immunisation is unequivocal [ 13 , 17 ], it is important to consider the impacts of mandates, including their unintended consequences. Although mandates are generally supported in Australia, debates around collective benefits versus individual choice highlight the need for ongoing evaluation [ 18 20 ]. A recent review of the literature found only two studies that specifically evaluated the NJNPlay legislation in isolation from NJNPay legislation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%